Merdeka Belajar Curriculum Policy Implementation: A Study of Teacher’s Perceptions in Senior High Schools of Konawe Regency - Samrin, Samrin; Alimuna, Wa; Awan, Rusdi (JURNAL AL-TANZIM, 2026)
This study is a qualitative descriptive research aimed at understanding teachers' perceptions of the "Merdeka Belajar" curriculum policy, particularly in relation to assessment, at public senior high schools (SMAN) in Konawe Regency. It also seeks to identify the challenges encountered in implementing this policy in the area of assessment. The sample in this study was selected using purposive sampling. Data collection methods included observation, interviews, and documentation, with interviews conducted using a structured set of questions. The results of the study indicate that teachers at SMAN in Konawe Regency have a positive perception of the "Merdeka Belajar" curriculum policy, especially regarding its application in assessment. However, several challenges were identified in its implementation, including: the diversity of student characteristics, teachers' limited understanding of the "Merdeka Belajar" curriculum policy in terms of both the teaching and assessment processes, low student motivation, unclear literacy materials, limited facilities and infrastructure, inadequate training provided by schools, and difficulties in conducting diagnostic assessments. To address these challenges, several solutions are proposed: Teachers should be more proactive in seeking information and knowledge about the "Merdeka Belajar" curriculum policy through online resources. Teachers should also participate more in training activities, both online and offline, to increase their understanding of the curriculum. Schools need to provide teaching materials and technological resources to support teachers. Furthermore, the professional development of teachers should be prioritized through ongoing educational initiatives.